Distribution of red cell antigens according to ABO, Rh and other rare blood group systems in Kurdish ethnicity - Hisham A Getta (Iraqi Journal of Hematology, 2016)
Background: Among more than 30 blood group systems, nine of them namely ABO, Rh, Kell, Kidd, Duffy, MNS, P, Lewis and Lutheran are considered to be clinically significant. The distributions of these blood groups are different between populations across the world. Studies about the frequency of blood groups in Kurdish ethnicity are very limited in the literature. Objectives: to explore the distribution of red cell antigens and phenotypes of various blood groups among Kurdish population using different systems. Materials and Methods: five thousand blood donors attending the central blood bank of Sulaymaniyah province were randomly selected and tested for ABO and Rh antigens (D, C, c, E, & e) by using tube method. 500 donors were randomly selected and further analyzed using other blood group systems. Results: In the ABO system, the most common phenotype was O (37%), followed by A (32.6%), B (22.8%) and AB (7.6%). Among the Rh blood group antigens, e was the most common (95.2%) followed by D (91.3%), C (74.8%), c (69.4%), and E (30.6%) with DCe/DCe(R1R1) and dce/dce(rr) being the most common phenotypes among Rh-D+ve and Rh-D-ve groups, respectively. The most common phenotypes for other blood systems were as follow; Kell(K-k+,94%), Kidd(jk a+b+,44.5%), Duffy(fy a+b+,45%), Lutheran(Lu a-b+,92%), Lewis(Le a-b+,54.5%), P(P1,76%), MNS(M+N+S-s+,40%) Conclusion: the various red cell antigens recorded by different blood grouping systems in this study was intermediate between the European and Asian countries with some specificity to the Kurds population reflecting the distinct geographical area and preserved ethnic background of the Kurds in the region.